2001
DOI: 10.1016/s0736-0266(00)00061-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydroxyapatite participate debris on the production of cytokines and proteases in human fibroblasts

Abstract: Cytokines and proteases are secreted by fibroblasts in response to particulate wear debris, and these proteins are felt to play an important role in the development of osteolysis and implant loosening. Although metallic and polyethlyene debris have been studied extensively, little is known about the cellular responses to hydroxyapatite, despite the wide clinical use of these materials. Therefore, the effects of hydroxyapatite (HA) and hydroxyapatitelp-tricalciumphosphate (HARCP) on cellular proliferation, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 43 publications
4
56
1
1
Order By: Relevance
“…This could explain the absence of "brous tissue between the cement and the bone observed during an in vivo study [1]. Nevertheless, it has been shown that CPC particles could stimulate the production of potent osteolytic cytokine by "broblasts [35].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This could explain the absence of "brous tissue between the cement and the bone observed during an in vivo study [1]. Nevertheless, it has been shown that CPC particles could stimulate the production of potent osteolytic cytokine by "broblasts [35].…”
Section: Discussionmentioning
confidence: 98%
“…The sterilization procedure used in this study was not designated to speci"cally remove the endotoxin from the particles, but was identical as for a clinical situation. Endotoxin could have been removed by successively treating the particles in nitric acid and ethanolic sodium hydroxide [35].…”
Section: Discussionmentioning
confidence: 99%
“…MMPs play an important role in the development of osteolysis and implant loosening, they can be produced after exposure to particles and they can be regulate by cytokines such as Interleukin-1 beta (IL-1β) an osteoclastic bone resorption stimulator [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Since macrophages have been observed to phagocytose debris particles, much attention has been focused on their role in cytokine production and osteoclast activation [ 1,6,27]. Although the fibroblasts comprise the largest component of periprosthetic tissues, there is only limited information about the role they play in the progression of aseptic osteolysis [23,28].…”
mentioning
confidence: 99%